Ten interleukins and risk of prostate cancer - Li, Bing-Hui; Yan, Si-Yu; Luo, Li-Sha; Zeng, Xian-Tao; Wang, Yong-Bo; Wang, Xing-Huan (Frontiers in Oncology, 2023)
Background: Evidence of previous observational studies on the associations between interleukins and prostate cancer risk are inconclusive. Methods: We conducted a bi-directional two-sample Mendelian randomization (MR) study to assess the causal associations between interleukins (ILs) and prostate cancer. Genetic instruments and summary-level data for 10 ILs were obtained from three genome-wide association meta-analyses. Prostate cancer related data were obtained from the PRACTICAL (79,148 cases and 61,106 controls), UK Biobank (7,691 cases and 169,762 controls) and FinnGen consortium (10,414 cases and 124,994 controls), respectively. Results: The odds ratios of prostate cancer were 0.92 (95% confidence interval (CI), 0.89, 0.96; P=1.58×10-05) and 1.12 (95% CI, 1.07, 1.17; P=6.61×10-07) for one standard deviation increase in genetically predicted IL-1ra and IL-6 levels, respectively. Genetically predicted levels of IL-1ß, IL-2a, IL-6ra, IL-8, IL-16, IL-17, IL-18, and IL-27 were not associated with prostate cancer risk. Reverse MR analysis did not find the associations between genetic liability to prostate cancer and IL-1ra (β, -0.005; 95% CI, -0.010, 0.001; P=0.111) and IL-6 (β, 0.002; 95% CI, -0.011, 0.014; P=0.755) risk. Conclusion: This MR study suggests that long-term IL-6 may increase the risk of prostate cancer and IL-1 inhibition may reduce it.